KRT5high TP63-expressing urothelial basal cells act as a driver to bladder urothelium regeneration in rabbit - Jiasheng Chen; Mingming Yu; Lin Wang; Hua Xie; Yiqing Lv; Yichen Huang; Yue Hong; Fang Chen (Stem Cell Research & Therapy)
Abstract Background Urothelial regeneration is a crucial part of bladder tissue engineering. However, there is a lack of ideal “seed cells” in current practices. Here, we demonstrated that a sub-population of p63 positive basal cells could be activated and differentiate into intermediate and superficial umbrella cells after full-thickness mucosal resection in rabbit. Methods A focal mucosal resection model was used to characterize the role of different urothelial cells during regeneration. Urothelial basal cells were isolated from rabbit bladder mucosa and cultured in vitro. The basal cells were then transplanted in vivo in a manner of cell sheet for reconstruction. Results Via single-cell RNA sequencing (scRNA-seq), it has been confirmed that the cluster of KRT5high TP63-expressing cells possesses a ‘‘stemness’’ signature which can give rise to lineage cell types sequentially. With a strong support from the underneath pre-set capsule vascular bed, the transplanted cell sheet could develop into a physio-morphology resembled to the native mucosa in vivo. Importantly, we validated that the bioengineered urothelium implemented perfect barrier function after implanted to bladder. Conclusions In summary, bioengineering urothelium with KRT5high TP63-expressing basal cells on a capsule vascular bed offers a promising strategy for bladder tissue engineering and provides a model for drug screening and bladder disease research.